Approach–avoidance behavior and motor‐specific modulation towards smoking‐related cues in smokers. - Song, Yuyu; Pi, Yanling; Tan, Xiaoying; Xia, Xue; Liu, Yu; Zhang, Jian (Addiction, 2023)
Aims: By performing three transcranial magnetic stimulation (TMS) experiments, we measured the motor‐specific modulatory mechanisms in the primary motor cortex (M1) at both the intercortical and intracortical levels when smokers actively approach or avoid smoking‐related cues. Design, Setting and Participants: For all experiments, the design was group (smokers versus non‐smokers) × action (approach versus avoidance) × image type (neutral versus smoking‐related). The study was conducted at the Shanghai University of Sport, CHN, TMS Laboratory. For experiment 1, 30 non‐smokers and 30 smokers; for experiment 2, 16 non‐smokers and 16 smokers; for experiment 3, 16 non‐smokers and 16 smokers. Measurements: For all experiments, the reaction times were measured using the smoking stimulus–response compatibility task. While performing the task, single‐pulse TMS was applied to the M1 in experiment 1 to measure the excitability of the corticospinal pathways, and paired‐pulse TMS was applied to the M1 in experiments 2 and 3 to measure the activity of intracortical facilitation (ICF) and short‐interval intracortical inhibition (SICI) circuits, respectively. Findings Smokers had faster responses when approaching smoking‐related cues (F1,58 = 36.660, P < 0.001, ηp2 = 0.387), accompanied by higher excitability of the corticospinal pathways (F1,58 = 10.980, P = 0.002, ηp2 = 0.159) and ICF circuits (F1,30 = 22.187, P < 0.001, ηp2 = 0.425), while stronger SICI effects were observed when they avoided these cues (F1,30 = 10.672, P = 0.003, ηp2 = 0.262). Conclusions: Smokers appear to have shorter reaction times, higher motor‐evoked potentials and stronger intracortical facilitation effects when performing approach responses to smoking‐related cues and longer reaction times, a lower primary motor cortex descending pathway excitability and a stronger short‐interval intracortical inhibition effect when avoiding them.